Salt Cooperatives as Public Credit Institutions for Coastal Communities: A Case Study of Two Salt Cooperatives in Rembang and Demak - Haryono Rinardi; Yety Rochwulaningsih (Journal of Maritime Studies and National Integration, 2017)
By using the historical method, the study discussing the existence of salt-producing community public cooperatives as micro credit institutions growing among coastal communities in Rembang and Demak. Both similarities and differences exist between the two. Both institutions (cooperatives are in need of government assistance. Both exist as a result of the hard work dedicated by the managers. The difference lies in the attitude of the villages’ administrators (bureaucrats)toward the existence of the cooperatives.